AKTIVITAS ANTIBAKTERI EKSTRAK PERASAN DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP Escherichia coli SECARA IN VITRO - Priamsari, Margareta Retno; Wibowo, Agastia Cicilia (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Noni juice can inhibit the growth of Escherichia coli bacteria. Noni juice extraction needs concentration to extract so that the preparation is more stable in the storage process. The purpose of this study was to determine the antibacterial activity and the amount of the minimum inhibitory concentration of noni juice extract from E. coli bacteria in vitro. This type of experimental research with a completely randomized one-way design. The extract was obtained by concentrating the Noni leaf extract. Extract quality control parameters include organoleptic, yield, drying shrinkage, and qualitative tests of flavonoid and anthraquinone compounds. Antibacterial activity test using the disc diffusion method with an extract concentration of 1.56%; 3.12%; 6.25%; 12.5%; and 25% with 3 replications. Positive control of amoxicillin and negative control of distilled water. Inhibition is known from the zone formed around the paper disc. The data obtained were statistically analyzed using Kruskall Wallis followed by Mann Whitney with a 95% confidence level. The results showed that the variation in the concentration of the noni juice extract had a significant effect (p <0.05). The biggest inhibitory zone was seen at 25% concentration of 10.16 mm and included in the strong category. The minimum inhibitory power was produced at a concentration of 3.12% at 2.50 mm with a weak treatment category.